Doa dalam Al-Qur’an: Studi terhadap Doa-Doa Para Nabi - Haikal Aby, Muhammad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Prayer constitutes the essence of worship in Islam and serves as a profound expression of faith, resilience, and spiritual submission. This study aims to unveil the multifaceted dimensions of the prophets’ prayers in the Qur’an by integrating the adābi ijtimāʾī approach of Tafsir Al-Azhar (Buya Hamka) and the lughāwī approach of Tafsir al-Kashshāf (Mahmud al-Zamakhsharī). Employing a qualitative descriptive design with library research and content analysis (tahlīlī-munaṣābah-semantik), primary data comprised Qur’anic verses featuring prophetic supplications. Analysis focused on etymological, morphological, rhetorical, and socio-cultural aspects, as well as the ethical etiquette (adab) and pedagogical functions embedded in each prayer. Findings reveal that prophets’ prayers encapsulate layers of linguistic eloquence, spiritual resilience, and communal guidance, while divine corrections within certain supplications underscore the pedagogical nature of revelation. This integrative tafsir framework offers a holistic model for incorporating Qur’anic supplications into contemporary character and academic education, fostering both linguistic insight and social relevance